Bad Boys: How Criminal Identity Salience Affects Rule Violation - Alain Cohn; Michel André Maréchal; Thomas Noll (Center for Economic Studies and ifo Institute (CESifo), 2015)
We conducted an experiment with 182 inmates from a maximum security prison to analyze the impact of criminal identity salience on cheating. The results show that inmates cheat more when we exogenously render their criminal identity more salient. This effect is specific to individuals who have a criminal identity, because an additional placebo experiment shows that regular citizens do not become more dishonest in response to crime-related reminders. Moreover, our experimental measure of cheating correlates with inmates' offenses against in-prison regulation. Together, these findings suggest that criminal identity salience plays a crucial role in rule violating behavior.
Keywords: K00; C93; K14; K42; Z10; 330; dishonesty; identity; crime; prison; experiment